Dynamics and prognostic value of the hypothalamus–pituitary–adrenal axis responses to pediatric critical illness and association with corticosteroid treatment: a prospective observational study - Jacobs, An (Intensive Care Med, 2019)
PURPOSE: Increased systemic cortisol availability during adult critical illness is determined by reduced binding-proteins and suppressed breakdown rather than elevated ACTH. Dynamics, drivers and prognostic value of hypercortisolism during pediatric critical illness remain scarcely investigated. METHODS: This preplanned secondary analysis of the PEPaNIC-RCT (N = 1440), after excluding 420 children treated with corticosteroids before PICU-admission, documented (a) plasma ACTH, (free)cortisol and cortisol-metabolism at PICU-admission, day-3 and last PICU-day, their prognostic value, and impact of withholding early parenteral nutrition (PN), (b) the association between corticosteroid-treatment and these hormones, and (c) the association between corticosteroid-treatment and outcome. RESULTS: ACTH was normal upon PICU-admission and low thereafter (p ≤ 0.0004). Total and free cortisol were only elevated upon PICU-admission (p ≤ 0.0003) and thereafter became normal despite low binding-proteins (p < 0.0001) and persistently suppressed cortisol-metabolism (p ≤ 0.03). Withholding early-PN did not affect this phenotype. On PICU-day-3, high free cortisol and low ACTH independently predicted worse outcome (p ≤ 0.003). Also, corticosteroid-treatment initiated in PICU, which further suppressed ACTH (p < 0.0001), was independently associated with poor outcomes (earlier live PICU-discharge: p < 0.0001, 90-day mortality: p = 0.02). CONCLUSION: In critically ill children, systemic cortisol availability is elevated only transiently, much lower than in adults, and not driven by elevated ACTH. Further ACTH lowering by corticosteroid-treatment indicates active feedback inhibition at pituitary level. Beyond PICU-admission-day, low ACTH and high cortisol, and corticosteroid-treatment, predicted poor outcome. This suggests that exogenously increasing cortisol availability during acute critical illness in children may be inappropriate. Future studies on corticosteroid-treatment in critically ill children should plan safety analyses, as harm may be possible. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00134-019-05854-0) contains supplementary material, which is available to authorized users.